2011
DOI: 10.1038/ijo.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

Body composition changes after laparoscopic adjustable gastric banding: what is the role of −174G>C interleukin-6 promoter gene polymorphism in the therapeutic strategy?

Abstract: Background: There is growing evidence that interleukin-6 (IL-6) is linked to the regulation of fat mass (FM). Our previous data define the common À174G4C IL-6 polymorphism as a marker for 'vulnerable' individuals at risk of age-and obesity-related diseases. An association between À174G4C IL-6 polymorphism and weight loss after bariatric surgery has been demonstrated. Objective: We investigated the impact of À174G4C IL-6 polymorphism on weight loss, body composition, fluid distribution and cardiometabolic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Although larger study populations are needed to confirm this observation, this finding is comparable with our previous study [10], which has reported the relationship between the −174 G > C polymorphism of IL-6 and therapeutic response to bariatric surgery.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although larger study populations are needed to confirm this observation, this finding is comparable with our previous study [10], which has reported the relationship between the −174 G > C polymorphism of IL-6 and therapeutic response to bariatric surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Poitou et al in 2005 showed a relationship between −174 G > C IL-6 polymorphism and circulating product in morbidly obese subjects, during weight loss after surgery [9]. In our previous study, at 6-month follow-up after LAGB surgery, according to IL-6 genotypes, no differences in fluid distribution were highlighted [10]. …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Resistance, reactance, impedance, phase angle, total body water (TBW), intracellular water (ICW), and extracellular water (ECW) were assessed by BIA phase sensitive system (BIA 101S, Akern/RJL Systems, Florence, Italy) [38, 39]. Impedance index (II) was evaluated with the following formula [40]: II=height2cm2resistanceΩ.…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations have shown that whole-body cryostimulation leads to an increase in the concentration of interleukin-6 (IL-6) [16,17]. Moreover, evidence indicates that IL-6 is linked to the regulation of fat mass [18]. Cryostimulation may intensify thermogenesis to maintain a balance between heat production and loss.…”
mentioning
confidence: 99%